2017
DOI: 10.1590/0102-33062016abb0450
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity and diversity of bryophytes in campos rupestres

Abstract: Campos rupestres (rupestrian grasslands) are characterized by the presence of rock outcrops associated with an herbaceous-shrub physiognomy typically growing on quartzitic soils; they occur a wide variety of habitats. Bryophytes respond rapidly and effi ciently to variation in microclimate. Th e present work aimed to study bryophyte species richness, diversity and composition, their life forms, and the substrates they colonize in exposed and shaded habitats in campos rupestres of Chapada Diamantina. Collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
2
2
0
8
Order By: Relevance
“…Other studies in Caatinga areas have, as in the present study, found greater species richness of mosses than hepatics Correia et al 2015;Valente et al 2017). This is probably due to the morphological complexity of mosses, which provides potential for occupying various environments ).…”
Section: Discussionsupporting
confidence: 65%
“…Other studies in Caatinga areas have, as in the present study, found greater species richness of mosses than hepatics Correia et al 2015;Valente et al 2017). This is probably due to the morphological complexity of mosses, which provides potential for occupying various environments ).…”
Section: Discussionsupporting
confidence: 65%
“…Campylopus surinamensis Müll.Hal. (Silva et al 2014), na Chapada Diamantina, Bahia e Minas Gerais (Valente et al 2017) e no Parque do Rola Moça e Parque Nacional Gandarela, Minas Gerais (Peñaloza-Bocajá et al 2017) (Fig. 3).…”
Section: Serra Sulunclassified
“…Constatando assim com outros trabalhos realizados em outras áreas de Caatinga e Cerrado do Nordeste RIOS et. al., 2016;VALENTE et. al., 2017;VIEIRA et.…”
Section: Resultsunclassified